Landscapes of unrest: Herbert Giersch and the origins of neoliberal economic geography - Dieter Plehwe; Quinn Slobodian (Modern Intellectual History, 2019)
This article bridges the gap between the intellectual history and critical geography of neoliberalism through a study of the overlooked figure of the German economist Herbert Giersch. As a public economist and director of the Kiel Institute for the World Economy from 1969 to 1989, Giersch blended German traditions of location theory with liberal globalism to lay the foundation of a neoliberal economic geography. We show the origins of globalism at Kiel through the work of the institute's founder, Bernhard Harms, and Giersch's influences, including Johann Heinrich von Thünen, August Lösch, and Alfred Weber. We argue that Giersch's neoliberal economic geography emerged out of two perceived necessities in the 1970s. On the one hand, he saw a need to reorient German industry through import competition with the global South. On the other hand, he felt the need for an ethically defensible global imaginary to pose against both traditional German social democracy and the promise of the global South's New International Economic Order. In his metaphor of a landscape of so-called Schumpeterian volcanoes in which regions were locked in perpetual struggle for temporary monopoly positions against competitors, Giersch provided a powerful distillation of the geographic imaginary at the heart of the neoliberal movement since the 1970s.
Additional information: Dieser Beitrag ist mit Zustimmung des Rechteinhabers aufgrund einer (DFG-geförderten) Allianz- bzw. Nationallizenz frei zugänglich / This publication is with permission of the rights owner freely accessible due to an Alliance licence and a national licence (funded by the DFG, German Research Foundation) respectively.
Keywords: 330; neoliberalism; economic geography; world economy; economic system; New International Economic Order; criticism